Establishment of a Special Fund to Provide Support for the Implementation of Measures for Environmental Protection and Remedying of the Consequences Arising From the Commitment of Criminal Offenses Against the Environment - Jeličić, Mladen (Glasnik Advokatske komore Vojvodine, 2026)
The author discusses the EU Directive 2024/1203 on environmental crime, which, among other things, recommends that member states establish a special fund that should have a dual function. First of all, its function is preventive, since the funds would be used to improve environmental protection measures and prevent the commission of environmental crimes. The remedial function of this fund would be manifested through the use of funds from the fund to remediate the consequences of environmental crimes. In the introduction, the author points out the importance of environmental protection and the malignancy of environmental crimes. Then, the purpose and standards of the aforementioned Directive are briefly outlined, as well as individual solutions from the Law on Environmental Protection that are significant for the topic of the paper. The author analyzes the feasibility of establishing a special fund and the legislative framework in the Republic of Serbia that would enable the implementation of this project. Possible ways of financing the aforementioned fund are indicated by analyzing the recommendations from the Directive regarding additional sanctions and measures that can be imposed on perpetrators and the confiscation of financial (property) gains obtained by committing a criminal offense. Other possible ways of financing the fund are also taken into account, as well as the criteria for using these funds. The author’s conclusion is that the establishment of a special fund for environmental protection and remediation of the consequences of environmental crimes can have significant positive effects, primarily in the preventive aspect, through the implementation of more efficient environmental protection measures, which should be the primary goal, but also in the remedial aspect, through the remediation of the consequences resulting from the commission of the aforementioned crimes.